2010
DOI: 10.1111/j.1600-0765.2010.01304.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of toll-like receptor 4 in alveolar bone loss and glucose homeostasis in experimental periodontitis

Abstract: Background and Objective There is general agreement that certain fatty acids and lipopolysaccharides (LPS) promote inflammation through toll-like receptor 4 (TLR4), and that inflammation promotes insulin resistance. We therefore hypothesized that mice with periodontitis and a TLR4 loss-of-function (LOF) mutation fed a high-fat (HF) diet would develop improved glucose homeostasis compared with wild-type (WT) animals with periodontitis fed a HF diet. Material and Methods Wild-type and TLR4 mutant mice fed a HF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 49 publications
4
42
0
Order By: Relevance
“…IR that developed in these animals was associated with a reduced phosphorylated Akt (p‐Akt)/Akt ratio in the liver upon stimulation with exogenous insulin 10 . The authors have also shown that insulin levels increase during IR/prediabetic development in this animal model 10,11 . Although LPS can stimulate the production of cytokines that promote IR in insulin target organs, 12,13 it has been shown that hyperinsulinemia drives the development of peripheral IR 14 .…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…IR that developed in these animals was associated with a reduced phosphorylated Akt (p‐Akt)/Akt ratio in the liver upon stimulation with exogenous insulin 10 . The authors have also shown that insulin levels increase during IR/prediabetic development in this animal model 10,11 . Although LPS can stimulate the production of cytokines that promote IR in insulin target organs, 12,13 it has been shown that hyperinsulinemia drives the development of peripheral IR 14 .…”
mentioning
confidence: 87%
“…Results from the authors’ previous studies 10,11 using an animal model indicate that IR develops in the setting of periodontitis induced by ligature placement and application of LPS around the gingival sulcus. IR that developed in these animals was associated with a reduced phosphorylated Akt (p‐Akt)/Akt ratio in the liver upon stimulation with exogenous insulin 10 . The authors have also shown that insulin levels increase during IR/prediabetic development in this animal model 10,11 .…”
mentioning
confidence: 99%
“…A number of studies have demonstrated that periodontitis lesions release high levels of these cytokines. Therefore, the basic premise underlying the potential influence of periodontitis on the diabetic condition is that proinflammatory cytokines or LPS released locally in gingiva may enter the systemic circulation and influence insulin target organs/tissues in distant sites 48 . Since TNFα is known to impair insulin signaling and cause insulin resistance 49 , it is hypothesized that periodontitis via production of TNFα and possibly other cytokines influences the diabetic condition.…”
Section: Possible Mechanisms Underlying These Two Way Relationshipsmentioning
confidence: 99%
“…For example, induction of periodontitis in prediabetic rats causes impaired glucose tolerance 51, 52 . In addition, induction of periodontitis accelerates the development of insulin resistance and the onset of T2DM in animals fed a high fat diet 48 . However, as mentioned above, more research is necessary to understand the inter-relationship between periodontitis and DM, especially the effect of periodontitis on the course of DM progression and end organ damage.…”
Section: Possible Mechanisms Underlying These Two Way Relationshipsmentioning
confidence: 99%
“…Results from our previous studies indicate that hyperinsulinemia develops when periodontitis is induced in rats and mice [7,8] and this finding is supported by results from studies that demonstrate that periodontitis promotes insulin resistance in a rat model in part via hyperinsulinemia [6,7]. …”
Section: Introductionmentioning
confidence: 53%